1982
DOI: 10.1111/j.1469-8137.1982.tb03380.x
|View full text |Cite
|
Sign up to set email alerts
|

The Assessment of Nitrogen Fixation and Throughput by Lichens

Abstract: SUMMARYThalli oi Peltigera membranacea, Peltigera polydactyla and Lobaria pulmonaria were labelled witĥ *N and subjected to simulated episodes of heavy rainfall after periods of drying in a lighted air-conditioned incubator. Inorganic and total nitrogen was estimated in the eluates. The drying-wetting cycle was repeated three times. From the level of ^^N labelling of the eluates, it was evident that recently fixed nitrogen was released, the inorganic fraction (NH4"^) being up to three times more heavily labell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 7 publications
0
18
0
Order By: Relevance
“…Kershaw (1985) reported that 19-28 % of labeled N applied to lichens was later found in surrounding soils. Earlier studies showed more N release when pH, temperature, light, CO 2 , or ionic conditions were suboptimal or during wetting after desiccation (Henriksson 1957;Jones and Stewart 1969a;Millbank 1982;Jeanfils and Rack 1992). Nitrogen release may occur very quickly once biocrust organisms become physiologically active.…”
Section: Nitrogen Release To the Surrounding Substratementioning
confidence: 97%
See 1 more Smart Citation
“…Kershaw (1985) reported that 19-28 % of labeled N applied to lichens was later found in surrounding soils. Earlier studies showed more N release when pH, temperature, light, CO 2 , or ionic conditions were suboptimal or during wetting after desiccation (Henriksson 1957;Jones and Stewart 1969a;Millbank 1982;Jeanfils and Rack 1992). Nitrogen release may occur very quickly once biocrust organisms become physiologically active.…”
Section: Nitrogen Release To the Surrounding Substratementioning
confidence: 97%
“…Extracellular release of nitrogenous compounds, including inorganic forms such as nitrate [NO 3 À ] and ammonium [NH 4 + ], and small amounts of amide, peptides, and free amino acids, occurs in both cyanobacteria and lichens (Stewart 1970;Millbank 1982). Nitrogen release is especially pronounced in the presence of N-fixing organisms, which can release 5-70 % of N fixed (Magee and Burris 1954;Silvester et al 1996).…”
Section: Nitrogen Release To the Surrounding Substratementioning
confidence: 99%
“…Extracellular release of nitrogenous compounds occurs in both cyanobacteria and lichens (Stewart 1970;Millbank 1982). It is especially pronounced in N-fixing organisms, which release 5-70 % of N fixed.…”
Section: Nitrogen Release To the Surrounding Substratementioning
confidence: 99%
“…Nutrients held in lichens positioned within the canopy are released into the forest system by intermittent leaching (Millbank, 1982). Lichens do not provide energy, nutrients or water directly to the vascular system of their host tree directly.…”
Section: Nutrient Dynamics Of Canopy Lichensmentioning
confidence: 99%
“…Nitrogen that is held in epiphytic lichens, and most importantly cyanolichens, can be released into the forest system and provide forest canopies and understory plants with N through intermittent leaching (Millbank 1982;Benzing 1990) and decomposition of lichen litterfall biomass (Campbell et al, 2010b). Research has established that nutrient leaching depends on lichen structure, amount of precipitation and surface area to volume ratio, but its quantification has not been properly assessed in sub-boreal forests of central BC.…”
Section: Introductionmentioning
confidence: 99%